Locating Human Resources to Reduce the Cost of Managing Networks of Protected Areas. Issue 6 (25th June 2014) - Dumoulin, Christine E.; Macmillan, Tyler; Stoneman, Rob; Armsworth, Paul R.
Abstract Conservation organizations that manage networks of protected areas commonly require staff to travel to those areas for management and monitoring purposes. We examine how conservation organizations can reduce the resulting travel costs by locating human resources effectively. Specifically, we focus on the problem of siting the home offices of management staff, in a way that minimizes the travel costs involved. We illustrate the importance of travel cost using two case study applications, the Yorkshire Wildlife Trust (YWT), U.K., and the Northwest Florida Water Management District (NWF), USA. For YWT, siting an additional office effectively could save 43, 000 in annual travel costs. Optimally, siting NWF's four existing offices could save 95, 000 annually. These savings are sufficient for each organization to acquire 171–360 additional hectares of protected area or to hire an additional protected area manager. We also calculated the reduction in greenhouse gas emissions made possible by optimizing office locations.